Understanding Culture - Labrador, Ana Maria Theresa (Social Science Diliman: A Philippine Journal of Society and Change, 2007)
Excerpt The word “culture” is now so much a part of the vocabulary of the prosaic that it could mean everything or nothing. It is sometimes compressed with art and sometimes distanced from it. Culture could also be a commodity in the same way that it is meant to be sold as a product to tourists and collectors.